Determinants of ICT adoption and uptake at a rural public-access ICT centre: A South African case study. Issue 6 (19th September 2022) - Frans, Cecilia; Pather, Shaun
Abstract : The global Covid-19 pandemic has created a heightened sense of awareness of the inequalities that prevail in society. Access to real-time information delivered via broadband internet has become critical for survival. However, the reality of the digital divide implies that some citizens, especially those in far-flung rural areas, are not as fortunate as others to be able to access such information given that internet access at a household level is only a reality across approximately 12% of South Africa. As such, the deployment of public-access ICT centres is still considered to be an important intervention by governments as a digital divide eradication strategy. However, the success of these initiatives is threatened by a lack of understanding of the issues relating to the adoption of ICTs in these communities. Qualitative data were collected via focus groups and the Unified Theory of Acceptance and Use of Technology (UTAUT) was applied as an analytical lens. The findings uphold the independent dimensions of UTAUT in explaining ICT adoption. The findings were also mapped to the Access, Capability and Environment (ACE). It was found that other external factors including those of corruption, training benefits and community exclusion are determinants of ICT adoption in a rural community.